Field measurement and questionnaire survey on indoor environment in typical coastal villages of Qingdao (China) during the heating period - Xudong Xie; Qianqian Yang; Weijun Gao (Case Studies in Thermal Engineering, 2021)
The rural living environment, especially for thermal environment and air quality, has always been concerned during the heating period. This study conducted a field measurement and questionnaire survey of indoor air quality in five villages in the cold rural coastal region of Qingdao, China. This area experiences the more extreme weather conditions, compared to the inland region. The sixty rural buildings were selected, while the basic characteristics, heating methods, indoor thermal environment, and air quality were recorded. Results showed the main heating method is the coal-fired stove combined with other radiators. The neutral values of indoor air temperature and relative humidity are 13 °C and 40% for local residents, which are much less than the comfortable levels. However, local residents demonstrated the ability to independently regulate temperature and humidity levels to within comfortable levels. And The coal combustion increases the indoor smell intensity and pollute indoor air. The CO2 concentration can be up to 1015.47 ppm and 690.78 ppm in rooms with and without the stove in the activity room respectively, while PM2.5 concentration can reach up to 199.6ug/m3 and 62.9ug/m3 respectively. These concentration values are much higher than the relative standards and the present air quality is very harmful to the human health.